Equilibrium Studies with Chlorate Ion in Mixed Aqueous Alcohols-The Effect of Temperature - Tomar, Radha; Bhatnagar, R.P. (Asian Journal of Chemistry, 2010)
Equilibrium studies with ClO3- ion in mixed solvents viz. aqueous methanol, aqueous ethanol and aqueous isopropanol have been performed using a strongly basic anion exchanger in nitrate form. Conclusions have been drawn regarding the variation of corrected selectivity coefficient with solvent composition. Effect of temperature on selectivity coefficient, variation of ΔF, ΔH, ΔS with solvent composition has also been studied.